Analyzing Praise Dynamics: Non-Native English Speakers' Use of Adjacency Pairs in Language Teaching at De Access Hotel and Culinary Training Centre - Wiratmoko, Gandung Aulia; Wijayanto, Agus; Laila, Malikatul; Radityo Tri Nugroho; Sari, Afifah Linda (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This research delves into the use of adjacency pairs in conversations between non-native speakers and EFL learners at De Access Hotel and Culinary Training Centre, employing discourse analysis. The study aimed to identify patterns of adjacency pairs in compliment exchanges and explore the preferred and dispreferred responses. Using a descriptive qualitative approach with a case study design, data were collected through passive observer participation observation during language classes. The researcher transcribed and analyzed spoken conversations, revealing consistent (Q – A) and (Q – A, Q – A, Q – A) patterns, emphasizing question-answer exchanges. Positive utterances (U) and non-verbal gestures (G) added diversity, while complex patterns like (Q (Q – A) A) and (U (Q – A) U) showcased layered interactions. The preferred response predominantly featured (Question – Answer), occurring seven times, followed by (Requesting – Acceptance) six times, while dispreferred responses were rare, primarily (Question – Unexpected Answer). This research provides English Department students with insights into adjacency pair patterns, preferred and dispreferred responses, enhancing classroom communication.